"Crimes against peace" and international law - Sellars, Kirsten (New York : Cambridge University Press, 2013)
'In 1946, the judges at the International Military Tribunal at Nuremberg declared'crimes against peace' - the planning, initiation or waging of aggressive wars - to be'the supreme international crime'. At the time, the prosecuting powers heralded the charge as being a legal milestone, but it later proved to be an anomaly arising from the unique circumstances of the post-war period. This study traces the idea of criminalising aggression, from its origins after the First World War, through its high-water mark at the post-war tribunals at Nuremberg and Tokyo, to its abandonment during the Cold War. Today, a similar charge - the'crime of aggression' - is being mooted at the International Criminal Court, so the ideas and debates that shaped the original charge of'crimes against peace' assume new significance and offer valuable insights to lawyers, policy-makers and scholars engaged in international law and international relations'--
The emergence of the concept of aggression -- The quest for control -- The creation of a crime -- Innovation and orthodoxy at Nuremberg -- The Allies and an ad hoc charge -- The elimination of militarism -- Questions of self-defence -- Divisions on the bench at Tokyo -- The uncertain legacy of'crimes against peace' -- Postscript.
Includes bibliographical references (pages 294-305) and index.
Keywords: Crimes against peace -- History; Aggression (International law) -- History; International criminal law -- History